Finitude, religião e transcendência: uma análise da condição humana em Ernest Becker - Almeida, Jussara Trindade de (2011)
This dissertation seeks to accomplish an analysis of the human condition in Ernest Becker (1924-1974) and the role of religion to sustain human beings in face of the fear of death and the precariousness of his creatureliness. The central object of research is his most important work, The Denial of Death. Initially, we present the main concepts of Becker used to describe the human existence: the creatureliness of human beings, torn between their animality and the self-consciousness that helped them to emerge from nature in comparison to all of the other animals; the existential paradox; the fear of life and fear of death which cause anxiety and the need to deny death; the twin ontological motives Eros and Agape that attract human beings in opposite directions; the basic need to feel a sense of self-worth and find meaning to human existence; the defense mechanisms used to repress from consciousness the fear of death and the reality of the creatureliness; the development of human character as a vital lie; the human dependence on and fascination with an external source power, related to the transference mechanism; and the oedipal transition that develops into the causa sui project, when the socialization of the individual occurs. Then we investigate Becker s view of religion and the reasons for considering it as one of the most effective ways of providing meaning to human life, as well as ideal forms of heroism that are not found in cultural hero systems and ways of transcending creatureliness symbolically. Finally, we present an outline of the heroic individual, the main reasons for Becker to glimpse the possibility of the fusion of psychology and religion, and a reflection on his expectations for this approach. It starts with the hypothesis that the possibility of heroism offered by religion is broader than the cultural forms, since religion takes into account the dimension of the invisible; also that the individuals can develop, with the support of religion, a greater strength to bear the contradictions of their human condition, together with a safer way to find meaning to their existences. We conclude that the Becker s heroic individual must have the courage that few possess to face anxiety, despite the support offered by religion and psychoanalysis